کلام اقبال کالسانی تجزیہ : ایک نیا ماڈل: The Linguistic Analysis of Iqbal's Poetry: A New Model (Research Journal Tahqeeqat, 2025)
Kaleemuddin Ahmed's contributions in the field of Urdu practical criticism hold a significant prominence, particularly in his critical analysis of both poetry and prose. Similarly, Meeraji's work Is Nazam Mein is highly regarded in the realm of Urdu literary criticism. Traditionally, Urdu texts have been evaluated either within the framework of Eastern literary contexts or through the lense of Western literary theories. However, there has been a lack of an integrated model that combines both approaches for a comprehensive evaluation of Urdu literature. This paper aims to bridge this gap by proposing a new model of literary criticism. This model seeks to combine the rich aesthetic methods of Eastern literary traditions with the structural analysis techniques rooted in Western scientific methodology. The study suggests a balanced approach that incorporates both these perspectives, offering a more holistic understanding of literary works. By doing so, it endeavors to enrich the field of Urdu criticism by utilizing modern approaches while preserving the essence of Eastern aesthetic sensibilities. This model will contribute to a deeper and more nuanced evaluation of Urdu texts, providing a framework for a critical analysis that is both global and rooted in cultural heritage.